Three-Dimensional Printing for Planning Occlusion Procedure for a Double-Lobed Left Atrial Appendage. (March 2016) - Fan, Yiting; Kwok, Ka-Wai; Zhang, Yiqun; Cheung, Gary Shing-Him; Chan, Anna Kin-Yin; Lee, Alex Pui-Wai
Abstract : Supplemental Digital Content is available in the text.